The principal’s role in promoting a revised model of teachers’ in-service professional development – the case of Israel - Oved, Sarah (Adult Education Discourses, 2020)
A 2008 report by Avney Rosha, the Israeli National Institute of School Leadership, to the Ministry of Education (MOE), outlined and redefined the principal’s role as a pedagogical leader. Among the expected outcomes from school principals at the start of their career is the professional development of the school staff. This paper will introduce a model of in-service professional development applied in the Israeli Education system: The Pedagogical Flexibility in Teachers’ Professional Development. This model has been applied and administered in Israeli schools by school principals recently. In addition, this paper will illuminate the two state reforms operating in the Israeli education system, which constitute one of the contexts in which principals work. It will be argued that among the plethora tasks school principals are in charge of, this task is less prioritised. Furthermore, it will be argued that implementing the model in the contexts in which Israeli schools operate, the education reforms and school practices limit the principal’s potential to maximise the benefits of this model, despite its significance to promote school outcomes.